Pengaruh Edukasi Screening HIV/AIDS Terhadap Sikap Ibu Hamil - Said, Fathia Fakhri Inayati; Makualina, Narli; Harini, Rika; Iksan, Ricky Riyanto (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Background: Acquired Immune Deficiency Syndrome (AIDS) is an infectious disease caused by the Human Immunodeficiency Virus (HIV). HIV/AIDS can be transmitted through blood transfusions, sexual intercourse, HIV-infected syringes, organ transplants and transmission from mother to fetus. To deal with transmission from mother to fetus, the government has a Triple Elimination program where pregnant women are required to undergo screening, one of which is HIV screening. /AIDS For this reason, education regarding HIV screening is needed to improve attitudes regarding HIV/AIDS screening in pregnant women. Research Objective: To determine the effect of HIV/AIDS screening education on the attitudes of pregnant women at the Sentani Community Health Center in 2023. Research Method: This research uses a pre-experimental design with a one group pretest – posttest design research design, the instruments used in this research were Lieflet and questionnaires. The sampling technique used purposive sampling as many as 72 respondents. Results: Data analysis using the Wilcoxon Signed Rank test showed that there was a difference in the mean value before (48.29) and after being given the HIV/AIDS Screening Education intervention for pregnant women (59.59) with an increase in the mean value of 11.3 with a significance value (p value) = 0.000 < 0.05 Conclusion: There is an influence of providing HIV/AIDS screening education on the attitudes of pregnant women. Keywords: Education, HIV/AIDS, Pregnant Women ABSTRAKAcquired Immune Deficiency Syndrome (AIDS) adalah sebuah penyakit menular yang disebabkan oleh virus Human Immunodeficiency Virus (HIV). HIV/AIDS dapat menular melalui transfuse darah, seksual, jarum suntik yang terinfeksi HIV, transplantasi organ dan penularann dari ibu ke janin, untuk menangani penularan dari ibu ke janin pemerintah memiliki program Triple Eliminasi dimana ibu hamil di wajibkan melakukan screening salah satunya yaitu screening HIV/AIDS  Untuk itu perlunya edukasi terkait screening HIV untuk meningkatkan sikap terkait screening HIV/AIDS Pada ibu hamil. Untuk mengetahui pengaruh edukasi screening HIV/AIDS terhadap sikap ibu hamil di Puskesmas Sentani 2023. Penelitian ini menggunakan desain Pre-eksperimental dengan rancangan penelitian one grup pretest – postest design, instrument yang digunakan pada penelitian ini adalah Lieflet dan kuesioner. tehnik pengambilan sampel menggunakan purposive sampling sebanyak 72 responden. Analisa data dengan uji Wilcoxon Signed Rank mendapatkan hasil adanya perbedaan nilai mean sebelum (48.29) dan sesudah diberikan intervensi Edukasi Skrining HIV/AIDS pada ibu hamil (59.59) dengan peningkatan nilai mean 11.3 dengan nilai signifikansi (p value) = 0.000 < 0.05. Adanya pengaruh pemberian edukasi skrining HIV/AIDS terhadap sikap ibu hamil. Kata Kunci: Edukasi, HIV/AIDS, Ibu Hamil